Origens da segregação racial no Brasil - Reinaldo José de Oliveira; Regina Marques de Souza Oliveira (Les Cahiers ALHIM)
The objective of this paper is to present the origins of segregation in Brazil, particularly the segregation of the black population. The approach follows the historic route of the years 1890 to 1930, marked by major changes in the Brazilian and Latin American scene: in 1888, the abolition of slavery, the following year the proclamation of the Republic and more precisely in the first decades of the twentieth century, the metamorphosis of industrial urban society, focusing in Salvador, Sao Paulo and Rio de Janeiro. We believe that racial segregation is structural and institutional therefore from 1870 until 1930 and, especially, in the course of the twentieth century and the present moment, the black population is in places of socio-economic and spatial inferiority. The Brazilian cities during the passage of the slave labor society to the free labor society, reproduces the logic of domination of the power of capital and inequality. In addition to the socioeconomic contradictions, is the body of the city that streamline places of racism that reflects the over-representation of black people in all spaces, places and territories.